Expert assessment of the suitability of treatment and diagnostic measures in providing emergency care to patients with acute coronary syndrome - Zabashta, Victoria; Fedak, Bogdan (ScienceRise: Medical Science, 2021)
It is known that it is possible to affect the extent of myocardial damage and, as a result, mortality only in the first hours of its development. Therapeutic tactics in ACS with elevation of the ST segment involves the restoration of coronary blood flow, the main method is the reperfusion of the coronary artery by systemic thrombolysis or PCI in a specialized hospital. The effectiveness of treatment is inversely related to the time spent. The aim of the study was to examine the opinion of specialists on the feasibility of implementing the items of the protocol of emergency medical care for patients with ACS at the place of call. Materials and methods. During the study the method of expert evaluations, which consisted of gathering information by interviewing experts and summarizing the individual opinions of experts into a general concept was used. The experts were 48 emergency physicians. The method of expert evaluation included the following stages: development of the questionnaire; survey of experts; summary of examination materials; calculation of statistical indicators; interpretation of the obtained results and formulation of conclusions. Results. In order to assess the actions of the emergency team, depending on the need to conduct them for diagnosis and emergency care for patients with ACS at the scene, we calculated the feasibility indexes for each item of the protocol. In the future, we divided the treatment and diagnostic measures for ACS with ST segment elevation according to the level of expediency at the scene into four groups (n): n1 – high level, n2 – sufficient level and n3 – low level and n4 – very low level. According to the results of the ranking, the scope of measures to be implemented by the head of the emergency team at the ACS with elevation of the ST segment on arrival on call, as well as measures that, according to interviewed experts, are not required at this stage and can be carried out during transportation of the patient to a specialized hospital. Conclusions. Based on the results of the calculation of feasibility indices and subsequent ranking of treatment and diagnostic measures for the relevant groups (n1, n2, n3, n4) from 37 items of the study, to assist patients with ACS with ST segment elevation at the scene, it is recommended to perform 16